Penerapan Digital Marketing Berbasis Media Sosial untuk Meningkatkan Daya Saing UMKM - Basar Maringan Hutauruk; Yohanes Herman Susilo; Asep Arwan Sulaeman; Atsal Naufal Lubis (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2026)
The rapid advancement of digital technology has significantly transformed marketing strategies for Micro, Small, and Medium Enterprises (MSMEs), with social media emerging as an effective platform for expanding market reach and enhancing business competitiveness. However, based on observations at SMK Garuda Nusantara and its partner MSMEs, the implementation of digital marketing remains limited due to low digital literacy, inadequate skills in branding, creative content development, and professional social media management. These limitations have resulted in low product visibility, limited customer engagement, and suboptimal business performance. This community service program aimed to enhance the competencies of vocational students and MSME owners in implementing social media-based digital marketing through training, mentoring, and technology implementation. The program adopted a participatory approach consisting of socialization, project-based learning, technology implementation, mentoring, evaluation, and sustainability activities. The training covered product branding, social media management, creative content creation, digital marketing strategy development, and social media analytics. The results indicated improved participants' understanding of digital marketing concepts, the establishment of active business social media accounts, enhanced quality of promotional content, and strengthened collaboration between students and MSMEs in supporting digital transformation. This program is expected to improve the competitiveness of MSMEs by promoting effective, innovative, and sustainable digital marketing practices.